Capital structure and the firm under uncertainty - Udo Broll; Kit Pong Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
This paper examines the interplay between the real and financial decisions of the competitive firm `a la Sandmo. Besides output price uncertainty, the firm faces additional sources of risk which are aggregated into an additive background risk. We show that the firm always chooses its optimal debt-equity ratio to minimize the weighted average cost of capital, irrespective of the risk attitude of the firm and the incidence of the multiple sources of uncertainty. Even though the introduction of the background risk affects neither the optimal debt-equity ratio nor the marginal rate of technical substitution, it does have an adverse effect on the output level of the firm. Furthermore, if capital is a normal input, the presence of the background risk induces the firm to acquire less capital by issuing less debt and equity.
Keywords: D81; G32; 330; Background risk; Capital structure; Price uncertainty